An Effective Training Model of Applied Basic Transactional Analysis Module to Improve Problem-solving Skill on Parent–Child Relationship in Indonesia - Maharatih, G A; Ismail, R I; Mansyur, M; Sudiyanto, A (KnE Life Sciences, 2019)
Knowledge and skills for psychiatrists on applied transactional analysis in Indonesia have not been studied extensively. Our study aimed to obtain an effective training model to improve knowledge and skills on applied basic transactional analysis (BTA) in Indonesia. The study was conducted on 72 psychiatric residents of Universitas Sebelas Maret and University of Indonesia. The subjects were randomized into training and reading groups of BTA module. The BTA knowledge and skills were evaluated with MCQ and OSCE. Cox Regression analysis was performed to evaluate the improvement and its affecting factors. There were significant differences regarding changes in knowledge evaluation and BTA skill before and after treatment with p<0.001; 95%CI: 2.63-6.06 and p<0.001; 95% CI=12.86 to 24.03, respectively. Training model treatment significantly improved BTA knowledge (Hazard ratio 2.54; 95% CI = 1.12 to 5.75; p = 0.026) and BTA skills (Hazard ratio = 4.37; 95% CI = 1.81 to 10.54; p = 0.001). Training model and module have been demonstrated to be able to improve BTA knowledge and skill two to four-fold compared to the reading model. Therefore this technique can be applied by psychiatrists and the curriculum of psychiatry residency education policy maker in Indonesia.